The Efffect of Financial Ratio on Profitability with NOM and GWM as Moderating Factors of Banking Financial Ratios ( Study at NTB Syariah Bank) - AZHAR SHAFIIN AZHAR SHAFIIN; Ahmad Amir Aziz; Sanurdi Sanurdi (UIN Mataram, 2023)
Profitability ratio is the main ratio in measuring the achievement of banking performance.Profitability ratio is influenced by several other ratios such as CAR, FDR, BOPO and NPF. Thisstudy examines and analyzes the effect of Capital Adequacy Ratio (CAR), Financing to DepositRatio (FDR), Operating Expenses to Operating Income (BOPO) and Non Performing Financing(NPF) on the profitability of PT Bank NTB Syariah with NOM (Net Operating Margin) andMinimum Reserve Requirement (GWM) as moderating. This research is a quantitative study thatwants to reveal the effect of financial ratios on profitability. The data used is the publication reportdata of PT Bank NTB Syariah for the period 2019 to 2021. The data analysis technique in thisstudy used Partial Least Square (PLS). The results showed that CAR, BOPO, NPF had nosignificant and negative effect on ROA as indicated by the P value of 0.212, 0.505 and 0.360respectively, while FDR had a significant and positive effect on ROA as indicated by a P value of0.000. For moderator variables, namely GWM and NOM, both have no significant effect inmoderating the FDR and BOPO variables, indicated by the P value of 0.988 and 0.589,respectively.